THE RECONSTRUCTION OF GEN Z STEREOTYPES IN JUMANJI: WELCOME TO THE JUNGLE (2017) BY JAKE KASDAN - Citra Alvisyahr; Atinia Hidayah (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2024)
This study is aimed to analyze: (1) Gen Z stereotype portrayed in Jumanji: Welcome to the Jungle (2017), (2) the reconstruction of Gen Z stereotype that is depicted in Jumanji: Welcome to the Jungle (2017). As the objective research, this study uses descriptive qualitative method to analyzed the film entitled Jumanji: Welcome to the Jungle (2017) directed by Jake Kasdan. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by using data collection, data reduction, data display, and conclusion. The researcher analyzes the data by using theory of popular culture, approaches on stereotype, and Gen Z stereotype. The result of the study: (1) Gen Z stereotypes portrayed in the Jumanji: Welcome to the Jungle (2017) such as concern about mental health, experience the negative impacts of technology, and thirst for validation. (2) the reconstruction of Gen z stereotype that is depicted in Jumanji: Welcome to the Jungle (2017), such as good problem-solving skill, confident, respectful and sense of empathy.